2010
DOI: 10.1158/0008-5472.can-08-2660
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutations in In situ and Invasive Breast Carcinomas

Abstract: The PIK3 signaling pathway has been identified as one of the most important and most frequently mutated pathways in breast cancer. Somatic mutations in the catalytic subunit of PIK3CA have been found in a significant fraction of breast carcinomas, and it has been proposed that mutant PIK3CA plays a role in tumor initiation. However, the majority of primary human tumors analyzed for genetic alterations in PIK3CA have been invasive breast carcinomas and the frequency of PIK3CA mutations in preinvasive lesions ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
77
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 17 publications
16
77
2
1
Order By: Relevance
“…The prevalence of PIK3CA mutations in this cohort (55%) is somewhat higher than that previously reported for DCIS (17-48%) 7,8,14,15,38,39 and invasive breast cancers (25-36%). 4,5,40,41 The relatively small number of cases included in this and other DCIS each studies (involving between six and 202 cases), 7,8,14,15,38,39 may account for the variation in prevalence.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The prevalence of PIK3CA mutations in this cohort (55%) is somewhat higher than that previously reported for DCIS (17-48%) 7,8,14,15,38,39 and invasive breast cancers (25-36%). 4,5,40,41 The relatively small number of cases included in this and other DCIS each studies (involving between six and 202 cases), 7,8,14,15,38,39 may account for the variation in prevalence.…”
Section: Discussioncontrasting
confidence: 75%
“…4,5,40,41 The relatively small number of cases included in this and other DCIS each studies (involving between six and 202 cases), 7,8,14,15,38,39 may account for the variation in prevalence. Alternatively, the high read-depth of our targeted sequencing may have led to increased detection rates compared with exome or Sanger studies: four DCIS cases had a PIK3CA variant frequency of o20%, which could have been missed by less sensitive methods.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[14][15][16][17] Accumulating evidence suggests that PIK3CA point mutations may also be common in other proliferative breast lesions such as benign papillomas and columnar cell lesions. [18][19][20][21][22][23] Prior studies have failed to identify PIK3CA mutations in histologically normal breast tissue, even with the same sensitive methods employed here.…”
Section: Discussionmentioning
confidence: 99%
“…3,12,13 We and other groups have previously shown that the PIK3CA genotype is concordant between ductal carcinoma in situ (DCIS) and concurrent invasive carcinoma in 66-100% of tested samples. [14][15][16][17] However, several small studies suggest that pre-neoplastic or benign breast lesions, such as papillomas, radial scars, or columnar cell lesions, may also very frequently harbor PIK3CA mutations. [18][19][20][21][22][23] The goal of this study was to systematically screen a large number of hyperplastic and putative precursor breast lesions, along with accompanying carcinomas for known activating mutations in PIK3CA and other key signaling molecules.…”
mentioning
confidence: 99%